TEACHERS’ MOTIVATION IN TEACHING EFL FOR STUDENTS WITH SPECIAL EDUCATIONAL NEEDS (SEN) AT SPECIAL SCHOOLS: A NARRATIVE INQUIRY IN INDONESIA - Amalia, Wafa; Kurniawan, Eri (International Journal of Education, 2025)
While there have been several studies reporting teachers’ teaching practices for students with special needs, the inquiry on teachers’ motivation in the realms of Indonesian special education and English as a Foreign Language (EFL) teaching on the basis of their vision on themselves, consisting of their ideal, ought-to, and feared language teacher selves is still lacking in literature. Motivation has been arguably a crucial factor in the teaching-learning dynamics. This study aims to dissect two Indonesian special school teachers’ motivation in teaching EFL to students with special educational needs (SEN) as it potentially drives them to develop professionally. This study, then, is executed as a narrative inquiry by amassing data from two Indonesian female special school teachers through interviews. The discoveries exhibit several elements which might motivate Indonesian special school teachers to teach EFL to students with SEN, encompassing (1) inspirations beyond educational environments, (2) adjustments to the curriculum, and (3) misalignments between the nationally administered curriculum and their teaching implementation. The aforementioned elements also accentuate how the diverse needs of students with SEN influence teacher motivation. In light to the inquiry, several recommendations are proposed for further studies.